Amylose-Lipid Complex as a Fat Replacement in the Preparation of Low-Fat White Pan Bread - Hee-Seon Lee; Kyung-Heon Kim; Sung-Hoon Park; Sung-Won Hur; Joong-Hyuck Auh (Foods, 2020)
Amylose-lipid complex (ALC) was prepared with corn starch and stearic acid and used as a shortening replacement in white pan bread preparation. ALCs were prepared using various concentrations of stearic acid to corn starch (1%, 3%, 5%, and 7%) under different temperatures (55, 65, and 75 °C) and for different durations of time (30, 60, and 120 min); then, their complexing properties were assessed using iodine reagent and X-ray diffraction. The complexing reaction at 75 °C for 60 min showed the highest complexing index of the tested conditions; the in vitro digestibility of ALC was lower than that of corn starch. White pan bread was prepared with ALCs and their characteristics, including appearance, loaf volume, and starch retrogradation during storage at room temperature for four days, were compared with those of control bread. With increasing ALC replacement concentrations, loaf volume and shape were significantly affected; however, starch retrogradation was significantly retarded and energy value decreased by ALC replacement. Overall, 50% replacement of shortening by ALC appeared to be a reasonable level for retaining the basic characteristics of the bread while retarding the staling process. These results indicate that ALCs may be potentially useful in the bakery industry for preparing low calorie and low-fat products.